ANALISIS PRINSIP GOOD COORPORATE GOVERNANCE DALAM PENGELOLAAN WAKAF PRODUKTIF DI YAYASAN SEKOLAH ISLAM TERPADU (SIT) AL-FURQON - Arta Amaliah Nur Afifah; Siti Rochmiyatun (Jurnal I-Philanthropy, 2021)
This study aims to reveal the management of productive waqf and the application of the Principles of Good Corporate Governance in the Management of Productive Waqf at The Al-Furqon Integrated Islamic School Foundation (IISF). Methods of data collection using field research techniques with interviews, observation, and documentation. Data analysis used a qualitative descriptive method with steps data reduction, data display, and conclusion drawing which showed that the management of productive waqf at The Al-Furqon Integrated Islamic School Foundation (IISF) had been managed properly and met the requirements indicators of the Principles of Good Corporate Governance. Application of the principles of transparency, accountability, responsibility, independency, and fairness can be applied in the productive waqf management system at The Al-Furqon Integrated Islamic School Foundation (IISF). Although the accountability principle has not fully fulfilled the Good Corporate Governance Principles.